Polyphyly of Boehmeria (Urticaceae) congruent with plastome structural variation - Zhan, Min; Xue, Ling; Zhou, Jian-Jun; Zhang, Qiang; Qin, Xin-Mei; Liao, Xiao-Wen; Wu, Lei; Monro, Alexander K.; Fu, Long-Fei (Frontiers in Plant Science, 2024)
Boehmeria is a taxonomically challenging group within the nettle family (Urticaceae). The polyphyly of the genus has been proposed by previous studies with respect to five genera (Debregeasia, Cypholophus, Sarcochlamys, Archiboehmeria and Astrothalamus). Extensive homoplasy of morphological characters has made generic delimitation problematic. Previous studies in other plant groups suggest that plastome structural variations have the potential to provide characters useful in reconstructing evolutionary relationships. We aimed to test this across Boehmeria and its allied genera by mapping plastome structural variations onto a resolved strongly supported phylogeny. In doing so, we expanded the sampling of the plastome to include Cypholophus, Sarcochlamys, Archiboehmeria and Astrothalamus for the first time. The results of our phylogenomic analyses provide strong support for Sarcochlamys as being more closely related to Leucosyke puya than to Boehmeria and for the clustering of Boehmeria s.l. into four subclades. The sizes of the plastomes in Boehmeria s.l. ranged from 142,627 to 170,958 bp. The plastomes recovered a typical quadripartite structure comprising 127~146 genes. We observe several obvious structural variations across the taxa such as gene loss and multiple gene duplication, inverted repeats (IRs) contraction and wide expansions, inversions. Moreover, we recover a trend for these variations that the early clades were relatively conserved in evolution, whereas the later diverging clades were variable. We propose that the structural variations documented may be linked to the adaptation of Boehmeria s.l. to a wide range of habitats, from moist broadleaf forests in Asia to xeric shrublands and deserts in Africa. This study confirms that variation in plastome gene loss/duplication, IR contraction/expansion, and inversions can provide evidence useful for the reconstruction of evolutionary relationships.